Subsampling Blood Swabs as an Efficient and Good Practice for RapidHIT ID® Analyses - Christian Siatka; Logan Privat; Anna Franzoni; Michele Rosso; Sylvain Hubac; Francis Hermitte (Forensic Sciences)
Background/Objectives: Rapid DNA instruments are gaining interest in the forensic community as a means of generating DNA profile information more quickly than standard laboratory workflows, and they have the potential to be carried out in decentralized structures of the main laboratory, such as in French overseas territories, where no laboratory facilities are installed. Although this system has been shown to be effective in analyzing rich traces (such as blood) sampled on a swab, it has the disadvantage of consuming the entire swab for analysis. Since it is impossible to double the sampling from very few blood stains, we designed a subsampling protocol of the main swab for analysis on RapidHIT ID® instruments. Methods: Two volumes of blood (10 µL and 150 µL) from four individuals were applied to a regular Copan flocked swab and then subsampled by three different operators using a Copan mini (subungual) flocked swab to recover a portion of the biological material. Results:The analysis of the mini swabs allows us to obtain a complete genetic profile regardless of the initial volume, with a better genetic profile intensity associated with a higher initial volume deposited on the regular swab. Conclusions: Therefore, this study presents a novel, effective, and adaptable subsampling method that has the potential to significantly improve forensic DNA analysis, particularly in remote or decentralized settings. It offers a flexible solution to current limitations of RapidHIT ID® technology and paves the way for future advancements in genetic forensic science.